Distance education: didactic resources, skills, attitudes and their relationship with independent study (Revista Electrónica Calidad en la Educación Superior, 2018)
Independent study as a fundamental element of distance education requires the individual's abilities and attitudes such as order, self-evaluation, ethics, communication, openness and self-esteem, thus increasing these variables during the processes of teaching and learning are directly related to the acquisition of knowledge and academic work. This research is qualitative of the non-experimental exploratory type and analyzes the experience of the students in the subject of Public Management that belongs to the Business Administration career with an emphasis in Business Administration of the School of Administration Sciences (ECA, for its acronym in Spanish) linked to the Written Material Production Program (PROMADE, for its acronym in Spanish) of the Directorate of Production of Didactic Materials (DPMD, for its acronym in Spanish). During the research, a survey was carried out to evaluate the didactic resource, the skills, the attitudes and their relationship with the independent study. The results were contrasted with the history of the approval indicators of the subject from the year 2013 to 2016.